Implementasi Manajemen Sistem Informasi Kearsipan Surat Masuk dan Surat Keluar di SMA Bina Muda Cicalengka - Habibah, Alma Nada; Setiawan, Heri (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
Background of the Study: This research is driven by challenges in managing incoming and outgoing mail archives at Bina Muda Cicalengka High School, which still relies on a manual system. This method results in slow processing, frequent recording errors, and a high risk of document loss. To address these issues, a computer-based digital archive information system was developed to enhance archival efficiency and security. Objectives: The study aims to design and implement a digital archive information system to streamline the processing of school correspondence archives. It also seeks to evaluate the system's impact on improving administrative performance and data integrity. Method: The research employed the waterfall development methodology, consisting of needs analysis, system design, implementation, and evaluation phases. Microsoft Visual Basic 6.0 was used as the development platform, Microsoft Access for database management, and Crystal Report for generating reports. Data collection involved literature reviews and document analysis to ensure alignment with archival standards and system requirement frameworks. Finding: The developed system successfully automated the documentation process, enhanced data security, and improved access to archival information. Key features include code standardization, master data management, transaction recording for incoming and outgoing mail, and comprehensive reporting functions. Performance evaluation indicated significant improvements in efficiency regarding time, labor, and resource utilization when compared to the previous manual system. Conclusion: Conclusion The implementation of the digital archive information system demonstrates a substantial advancement in administrative governance for educational institutions. It highlights the critical importance of adopting digital solutions to ensure efficient, secure, and standardized archival management in the digital era.